THE RELATIONSHIP BETWEEN HEALTH WORKER SUPPORT AND ADHERENCE TO TAKING HYPERTENSION MEDICATION AT BEKASI JAYA HEALTH CENTER, EAST BEKASI 2023 - Prasetya, Anisya; Lina Indrawati; Roulita (Rena Cipta Mandiri, 2024)
Backround : Compliance with medication among hypertensive patients is a crucial factor in improving their health and quality of life. Family and healthcare providers can significantly influence blood pressure reduction programs. Successful treatment can only be achieved through collaboration between patients, healthcare providers, and families. Healthcare provider support plays a significant role in preventing hypertension, such as through health education, awareness campaigns, and early detection. Purpose : This research aims to determine the relationship between healthcare provider support and medication adherence among hypertensive patients at Bekasi Jaya, East Bekasi Public Health Center. The study was conducted from May 3rd to June 3rd. Methode : This is a quantitative research using a cross-sectional method. The research population consists of registered hypertensive patients at Bekasi Jaya, East Bekasi Public Health Center, with a sample size of 123 individuals who meet the inclusion and exclusion criteria. The sampling technique used is simple random sampling. Result : The research results indicate that the significance value of the relationship between healthcare provider support and medication adherence is p-value (0.000) < (0.005), indicating that H0 is rejected, meaning there is a relationship between healthcare provider support and medication adherence among hypertensive patients in Bekasi Jaya, East Bekasi in 2023.